2013
DOI: 10.1111/dsu.12067
|View full text |Cite
|
Sign up to set email alerts
|

Banana Leaves As an Alternative Wound Dressing

Abstract: We found banana leaves to be an excellent alternative wound dressing, combining the desirable properties of modern wound-dressing material with low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…The pain was so intense, the patient refused to be treated at times. However, after changing to banana leaf dressing, the patient reported a decrease in pain level during wound management, which correlated to the results from previous researches [11,12]. It was suggested that pain relief that comes with the use of banana leaf was due to water and fiber component of the leaf which help reduce the friction between the wound and dressing.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The pain was so intense, the patient refused to be treated at times. However, after changing to banana leaf dressing, the patient reported a decrease in pain level during wound management, which correlated to the results from previous researches [11,12]. It was suggested that pain relief that comes with the use of banana leaf was due to water and fiber component of the leaf which help reduce the friction between the wound and dressing.…”
Section: Discussionsupporting
confidence: 79%
“…The decrease of pain level and the increase of ease and speed are statistically significant when sterile banana leaf dressing is used in wound management. However, the caution in using banana leaf dressing is infections from contamination; it is advised to use only leaves that have been sterilized for no more than 2 days [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other remedies such as banana leaves appear as valid alternative agents for wound dressing [43] .…”
Section: T R O P I C a L S K I N I N F E C T I O N S O F Immigrantsmentioning
confidence: 99%
“…), Gram-positive cluster-forming cocci (mainly Micrococcus spp.) and molds [5]. Of importance, contaminants likely include potentially pathogenic organisms, such as anaerobic sporeforming bacilli (e.g., Clostridium spp.).…”
mentioning
confidence: 99%
“…According to generally accepted standards, wound dressings as a class of medical device are classified as 'critical', meaning they must be sterile. In a recent study, we compared different thermal decontamination (cooking in boiling, chemical disinfection, sterilization) to identify the optimal procedure for reducing the natural microbial load of the leaves without significantly affecting their beneficial wound-dressing properties [5]. Steam sterilization (autoclaving) resulted in the complete inactivation of mesophilic bacteria and sterile banana leaves.…”
mentioning
confidence: 99%